Risk assessment in chemical carcinogenesis - Schettler, Gotthard; Schmähl, Dietrich; Klenner, Thomas (Sitzungsberichte der Heidelberger Akademie der Wissenschaften, Mathematisch-Naturwissenschaftliche Klasse, 1991)
The essays in this book discuss the role that chemical agents in the environment play in the development of cancer. Thus, it gives information toimprove our understanding of carcinogenesis and how to prevent it. The essays were originally presented at an international symposium
Keywords: Konferenzschrift -- 1990 -- Heidelberg; Carcinogenese; Umweltchemikalie